PERAN TRANSPORTASI ONLINE DALAM MENUNJANG AKTIVITAS MASYARAKAT DAN MENJAGA EKSISTENSI PASCA PANDEMI COVID-19 DI KOTA BEKASI - Budi Purwoko; Chotib; Lin Yola (DAS Institute, 2022)
This research aims to examine the existence of online transportation in the community due to technological developments and the Covid-19 pandemic storm. Spatial policy with transportation policy is very closely related. City land provides space as a place of activity, while transportation acts as a network (network) connecting between spaces. The re-arrangement of transportation towards the use of space is a focus that must be done immediately after the Covid-19 pandemic. This research uses qualitative methods. The results of this study are steps taken by related parties to create online transportation services and bekasi city spaces that are comfortable for the activities of their citizens and the construction of sustainable urban spaces after the Covid-19 pandemic. There is a synergy of policies both by the Government, Society and Operators as transportation service providers so that the role of online transportation in supporting community activities can be fulfilled.